Analysis of Science Literacy Skill of Chemistry Education Students of Tanjungpura University - Resi Febriyanti; Husna Amalya Melati; Erlina Erlina; Rachmat Sahputra; Maria Ulfah (Universitas Lampung, 2021)
Abstract: Analysis of Science Literacy Skill of Chemistry Education Students of Tanjungpura University. Scientific literacy skill is one of the abilities that must be possessed by Chemistry Education students as prospective teachers. This research employs a quantitative descriptive method which aims to analyze the scientific literacy skills of the Chemistry Education students of Tanjungpura University. Fourty-three students in the fourth year of the 2020/2021 academic year participated in this study. Scientific literacy tests, questionnaires and interviews were used as to collect the data. The scientific literacy test is used to measure aspects of knowledge and competence which adopted from the Dutch National Chemistry Exam consisted of 16 questions. The 11 statements in the questionnaires are used to measure the aspects of attitudes. Interviews are used to confirm the results of both test and questionnaire. Data were analyzed by calculating the test scores and the percentage of students’ answers on the questionnaire. Based on data analysis, students' scientific literacy skills of knowledge and competence aspect are classified as low with an average score of 43 and 38, while the attitude aspect is classified as moderate with an average percentage of 75%. Students' scientific literacy skills in both aspects need to be improved through the integration of scientific literacy in the learning process and in the use of learning media.Keywords: science literacy skills, prospective chemistry teacher, quantitative descriptiveDOI: 10.23960/jppk.v10.i3.2021.09